Layered Metal Thiophosphite Materials: Magnetic, Electrochemical, and Electronic Properties - Mayorga-Martinez, Carmen C; Sofer, Zdeněk; Sedmidubský, David; Huber, Štěpán; Eng, Alex Yong Sheng; Pumera, Martin (ACS applied materials & interfaces, 2017)
Beyond graphene, transitional metal dichalcogenides, and black phosphorus, there are other layered materials called metal thiophosphites (MPSx), which are recently attracting the attention of scientists. Here we present the synthesis, structural and morphological characterization, magnetic properties, electrochemical performance, and the calculated density of states of different layered metal thiophosphite materials with a general formula MPSx, and as a result of varying the metal component, we obtain CrPS4, MnPS3, FePS3, CoPS3, NiPS3, ZnPS3, CdPS3, GaPS4, SnPS3, and BiPS4. SnPS3, ZnPS3, CdPS3, GaPS4, and BiPS4 exhibit only diamagnetic behavior due to core electrons. By contrast, trisulfides with M = Mn, Fe, Co, and Ni, as well as CrPS4, are paramagnetic at high temperatures and undergo a transition to antiferromagnetic state on cooling. Within the trisulfides series the Néel temperature characterizing the transition from paramagnetic to antiferromagnetic phase increases with the increasing atomic number and the orbital component enhancing the total effective magnetic moment. Interestingly, in terms of catalysis NiPS3, CoPS3, and BiPS4 show the highest efficiency for hydrogen evolution reaction (HER), while for the oxygen evolution reaction (OER) the highest performance is observed for CoPS3. Finally, MnPS3 presents the highest oxygen reduction reaction (ORR) activity compared to the other MPSx studied here. This great catalytic performance reported for these MPSx demonstrates their promising capabilities in energy applications.
Keywords: oxygen reduction reaction; metal phosphorus chalcogenides; oxygen evolution reaction; two-dimensional materials; hydrogen evolution reaction